1984
DOI: 10.1021/bi00296a012
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and phase transfer of nucleic acids by gramicidin S

Abstract: A novel interaction between gramicidin S (GrS) and nucleic acids is characterized which, like that between GrS and nucleotides, exploits both the dicationic and amphiphilic properties of the peptide. Complex formation between calf thymus DNA and GrS is demonstrated by (i) phase transfer to CHCl3 of ultrasonically irradiated DNA and (ii) inhibition of phase transfer to CHCl3 of adenosine 5'-triphosphate by either native or ultrasonically irradiated DNA. The stoichiometry of the interaction is 2:1 (DNA-P:GrS), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Given the high affinity of GS to bind to and permeabilize lipid membranes532, and in view of its dangerous potential to deactivate629 and delocalize7 membrane proteins, the question arises as to how GS can be stored without affecting the cells during biosynthesis. Based on its intrinsic affinity for anionic compounds, the binding of GS to S-layer proteins, phospholipids, and/or nucleic acids had been suggested93334, but early TEM studies had not revealed any GS-containing subcellular structures that accumulate GS9. Here, we have demonstrated that specific granules containing GS and alkyl phosphates are formed in GS-producing phenotypes of A. migulianus to fulfil this task.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high affinity of GS to bind to and permeabilize lipid membranes532, and in view of its dangerous potential to deactivate629 and delocalize7 membrane proteins, the question arises as to how GS can be stored without affecting the cells during biosynthesis. Based on its intrinsic affinity for anionic compounds, the binding of GS to S-layer proteins, phospholipids, and/or nucleic acids had been suggested93334, but early TEM studies had not revealed any GS-containing subcellular structures that accumulate GS9. Here, we have demonstrated that specific granules containing GS and alkyl phosphates are formed in GS-producing phenotypes of A. migulianus to fulfil this task.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, complexation and phase transfer of DNA by gramicidin S have been reported. 69 Spore preparations from B . brevis contain large amounts of gramicidin S bound avidly to the outer surface of the spore.7o The bound antibiotic is responsible for (1) the high cell surface hydrophobicity of the ~p o r e s ,~' and ( 2 ) causing a long delay in spore germination o~t g r o w t h .~~~~~ Mutants lacking gramicidin S germinate rapidly and do not have a lipophilic surface (measured by binding to he~adecane).…”
Section: A Gramicidin Smentioning
confidence: 99%
“…One of these early studies described inhibition of proteins in the membrane of its producer strain ( 38 ), and recently, it was shown that gramicidin S interferes with the membrane binding of the cell wall synthesis enzyme MurG and the electron transport chain protein cytochrome c ( 39 ). It has also been reported that both gramicidin S and the tyrocidines bind to DNA in vitro , suggesting an alternative or additional killing mechanism ( 40 43 ).…”
Section: Introductionmentioning
confidence: 98%